2014
DOI: 10.1038/srep07396
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of the Th17-IL-6R/pSTAT3/BATF/RorγT-axis in the tumoural region of adenocarcinoma as compared to squamous cell carcinoma of the lung

Abstract: Here we describe increased expression of IL6R in the tumoural region of lung tissue from patients affected by lung adenocarcinoma as compared to squamous cell lung carcinoma. Moreover, here we found increased IL6R in the tumour free part of the lung. By using a murine model of lung adenocarcinoma, we discovered that few lung tumour cells expressed IL-6R and CD4+CD25+Foxp-3+ T regulatory cells down-regulated IL-6R in the tumour bearing lungs. Downstream of IL-6R, the Th17 lineage-specification factors: Signal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…This immune evasive mechanism has been known to be hijacked by many kinds of tumors, including NSCLC, where upregulation of the immune checkpoint axis has been reported. 6,28 Although clinical trials with immune checkpoint inhibitors showed promising results, not all patients have been benefited and the need of patient selection for personalized treatment is being advocated. Recent data showed that patients with upregulation of the immune checkpoint axis before treatment may have higher response.…”
Section: Discussionmentioning
confidence: 99%
“…This immune evasive mechanism has been known to be hijacked by many kinds of tumors, including NSCLC, where upregulation of the immune checkpoint axis has been reported. 6,28 Although clinical trials with immune checkpoint inhibitors showed promising results, not all patients have been benefited and the need of patient selection for personalized treatment is being advocated. Recent data showed that patients with upregulation of the immune checkpoint axis before treatment may have higher response.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the material and methods related to the human studies where recently reported in details. 3,35,36,45,46 Total cells isolation from human lung samples Samples were cut into very small pieces using scalpels (1-3 mm 2 ). The shredded material was then subjected to collagenase/DNase digestion (20 ml solution per 1 g of material) and incubated over night at 37 C under constant shaking (300 r.p.m).…”
Section: Human Subjects and Study Populationmentioning
confidence: 99%
“…In addition, we also identified several genes primarily associated with LUAD. According to Balabko et al (2014) RORC is a specific transcription factor in the tumor area of lung tissue in patients with LUAD. DLX5 (Kato et al, 2008;Balabko et al, 2014), MUC1 (Mashima et al, 2005;Molina-Pinelo et al, 2014), and KRT17 (Erdogan et al, 2009;Liu et al, 2018) were found to be overexpressed in LUAD.…”
Section: The Biological Significance Of the Identified Signaturementioning
confidence: 99%